단삼이 활성산소에 의하여 손상된 배양 해마신경세포에 미치는 영향 - 이병찬(Byung Chan Lee); 한선희(Sun Hee Han); 송인영(In Young Song); 이강창(Kang Chang Lee) (동의생리병리학회지, 2003)
In order to evaluate the cytotoxic effect of reactive oxygen species(AOS), the cell viability was measured by MTT assay after cultured mouse hippocampal neurons were treated with various concentrations of xanthine oxidase(XO) and hypoxanthine (HX) for 5 hours. And also, the protective effect of Salviae Mutiorrhizae Radix(SMR) on XO/HX-induced neurotoxicity was examined in these cultures. XO/HX significantly decreased cell viability in dose-and time dependent manners when cultured mouse hippocampal neurons were treated with 5～40 mU/ml XO for 5 hours. In the protective effect of SMA, SMR increased cell viability dose-dependently after cultured mouse hippocampal neurons were preincubated with 30～120 ㎍/ml SMR for 2 hours. From these results, it is suggested that XO/HX is toxic on cultured mouse hippocampal neurons, and herbe medicine such as SMR is very effective in blocking the cytotoxicity induced by AOS.